Teacher Leadership and School Climate Effects on Learning Quality: An Indonesian Case Study - Marsalina Way; Yuni Astuti (Papanda Publisher, 2026)
This study investigates the influence of teacher leadership and learning climate on learning quality at SMP Negeri 1 Sorong Regency, Indonesia. Employing a quantitative survey design, data were collected from 202 students through validated questionnaires (Cronbach's α > 0.80) and observational assessments of 41 teachers. Multiple linear regression analysis was used to examine both partial and simultaneous effects. Results revealed that teacher leadership significantly and positively influenced learning quality (β = 0.222, t = 3.962, p < 0.001), as did learning climate with substantially greater magnitude (β = 0.626, t = 11.113, p < 0.001). Simultaneously, both variables explained 63.9% of learning quality variance (R² = 0.639, F = 175.847, p < 0.001), with learning climate emerging as the dominant predictor. These findings demonstrate that while effective teacher leadership enhances learning quality through classroom management, motivational communication, and instructional guidance, learning climate exerts primary influence by providing psychologically safe, inclusive, and supportive environments essential for student engagement and achievement. The dominance of learning climate in Indonesia's multicultural educational context challenges Western-centric frameworks prioritizing leadership over environmental factors. Practical implications suggest educational stakeholders should prioritize climate enhancement initiatives while simultaneously strengthening teacher leadership capacities to optimize learning quality in diverse educational settings.